Pharmacokinetic Study of Coadministration with Cefuroxime Sodium for Injection Influencing ReDuNing Injection-Derived Seven Phytochemicals and Nine Metabolites in Rats. (2nd July 2022) - Zhao, Qiulong; Wang, Chunxue; Cheng, Jiaxin; Yan, Hui; Wang, Ling; Qian, Dawei; Duan, Jinao
Abstract : According to the sixth edition of China's "New Coronavirus Diagnosis and Treatment Plan (NCDTP), " ReDuNing injection (RDN) was firstly introduced to treat severe and critical COVID-19, whereas its combination with broad-spectrum antibiotics was suggested to take with extreme caution and full reasons. Therefore, we aim to describe the pharmacokinetics of seven active phytochemicals and semiquantification of nine relevant metabolites in ReDuNing injection (RDN) after combining with cefuroxime sodium (CNa) for injection in rat plasma. Male Sprague–Dawley rats were randomly assigned to six groups, and they were intravenously administered, respectively, with different prescriptions of RDN (2 mL/kg) and CNa (225 mg/kg). At different time points (0.03, 0.08, 0.17, 0.24, 0.33, 0.50, 0.67, 1, and 6 h) after administration, the drug concentrations of iridoids glycosides, organic acids, and metabolites in rat plasma were determined using ultrahigh-pressure liquid chromatography coupled with linear ion rap-orbitrap tandem mass spectrometry (UHPLC–LTQ–Orbitrap–MS), and main pharmacokinetic parameters were estimated by noncompartment model. The results showed that there were differences in pharmacokinetic parameters, AUC(0-t), T1/2, C max, CL of iridoids glycosides, and organic acids, after the intravenous administration of the different combinations of RDN and CNa. Moreover, different combinations of the injections also resulted in different curves of relative changes of each metabolite. The obtained results suggested that RDN and CNa existed pharmacokinetic drug–herb interactions in rats. The findings not only lay the foundation for evaluating the safety of RDN injection combined with CNa but also make contributions to clinically applying RDN injection combined with CNa, which works potentially against severe forms of COVID-19.